2022 IEEE 19th Annual Consumer Communications &Amp; Networking Conference (CCNC) 2022
DOI: 10.1109/ccnc49033.2022.9700713
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Electric Vehicles on The Go

Abstract: When citing, please refer to the published version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Using an off-the-shelf IoT reader on the interface is generally impossible. As a result, access to the OBD-II data requires a customized IoT device [65]. Studies have also revealed that in order to examine different driving styles, the battery data sampling range should be between 0.1 and 3 s [46].…”
Section: The Ev Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an off-the-shelf IoT reader on the interface is generally impossible. As a result, access to the OBD-II data requires a customized IoT device [65]. Studies have also revealed that in order to examine different driving styles, the battery data sampling range should be between 0.1 and 3 s [46].…”
Section: The Ev Datasetmentioning
confidence: 99%
“…Meanwhile, SOH analysis requires the fine-time granularity of the acquired data (e.g., 250 ms sample rate). Currently, internet of things (IoT) devices can perform data collection in various situations and on precise time scales [65]. However, many automotive electronic control units (ECUs) can only operate at a lower sample rate due to the heavy load on the automobile's ECU.…”
Section: Introductionmentioning
confidence: 99%